Diagnosis and Treatment of Digestive System Disorders in Reptiles - Rizzo, Toni (MD Conference Express, 2014)
Digestive system disorders in reptiles are a diagnostic challenge because of the variations in gastrointestinal (GI) anatomy and physiology among species of reptiles. This article presents an update on the latest advances in diagnostic techniques and therapy that have provided practicing veterinarians with tools for improved diagnosis and treatment of GI disorders in reptiles commonly maintained as companion animals.